2015
DOI: 10.1063/1.4923315
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of thermally-activated artificial muscles based on coiled nylon fishing lines

Abstract: The discovery of an innovative class of thermally activated actuators based on twisted polymeric fibres has opened new horizons toward the development of effective devices that can be easily manufactured using inexpensive materials such as fishing lines or sewing threads. These new devices show large deformations when heated together with promising performance in terms of energy and power densities. With the aim of providing information and data useful for the future engineering applications, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 11 publications
(12 reference statements)
2
50
0
2
Order By: Relevance
“…Above a certain pre-load level the contraction strains remain constant since the full contraction can be achieved without coil-coil contact. Isometric actuation tests [19] have shown that the force generated increases linearly with temperature and the force -temperature coefficient increases only slightly with increasing pre-loading. The near independence of actuator strain and stress generated of polymer coil muscles on pre-load is unusual, as most artificial muscles show a decreasing actuation response with an increase in pre-…”
Section: Actuation Performance Of Polymer Coil Musclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Above a certain pre-load level the contraction strains remain constant since the full contraction can be achieved without coil-coil contact. Isometric actuation tests [19] have shown that the force generated increases linearly with temperature and the force -temperature coefficient increases only slightly with increasing pre-loading. The near independence of actuator strain and stress generated of polymer coil muscles on pre-load is unusual, as most artificial muscles show a decreasing actuation response with an increase in pre-…”
Section: Actuation Performance Of Polymer Coil Musclesmentioning
confidence: 99%
“…Actuation studies reported to date for polymer coil muscles have only considered the isotonic (∆F A =0) [14] or isometric (∆L A =0) [19] actuation behaviors. These studies have investigated the effect of pre-stretch on the isotonic actuation strain (Fig.…”
Section: Actuation Performance Of Polymer Coil Musclesmentioning
confidence: 99%
“…Although a number of methods exist [4], [5], [16], [20], the simplest application oriented method is Joule heating with a resistance wire. Wrapping the resistance wire around the polymer, as illustrated in Fig.…”
Section: A Working Principlementioning
confidence: 99%
“…Training of the muscle is usually seen as repeating the actuation cycle in the setup a number of times before performing the actual experiment [5], [20], [21]. We let muscles undergo a number of cycles of heating and cooling, from room temperature to the maximum actuation temperature, in the intended setup.…”
Section: Trainingmentioning
confidence: 99%
See 1 more Smart Citation